Leaf Spot and Dry Fruit Rot of Pomegranate: Biology, Epidemiology and Management - Kumari, Neelam (International Journal of Economic Plants, 2017)
Pomegranate (Punica granatum L.) diseases often caused by a range of fungi and bacteria, pose direct significant financial, nutritional and postharvest losses. Common fruit rot pathogens of pomegranate include Botrytis cinerea, Alternaria alternata, Penicillium implicatum, Coniella granati and Aspergillus niger. Pomegranates are highly susceptible to fruit rot caused by Coniella granati (Sacc.) Petrak and Sydow and the disease is assuming importance in Himachal Pradesh due to its severity. This review discusses the leaf spot and dry fruit rot of pomegranate caused by Coniella granati, its symptomatology, epidemiology and management.